The green tea component (−)-epigallocatechin-3-gallate protects against cytokine-induced epithelial barrier damage in intestinal epithelial cells - Rosenthal, Rita; Waesch, Anne; Masete, Kopano Valerie; Massarani, Alain S.; Schulzke, Jörg-Dieter; Hering, Nina A. (Frontiers in Pharmacology, 2025)
BackgroundGreen tea consumption is associated with health benefits, which are mainly attributed to its catechins, especially the main catechin (−)-epigallocatechin-3-gallate (EGCG). Among other beneficial effects, EGCG was shown to be protective in inflammatory bowel disease (IBD), a condition associated with barrier dysfunction. To elucidate the mechanisms behind this, the present study analyzed the impact of EGCG on barrier properties and inflammatory cytokine-induced barrier dysfunction in three different intestinal cell models.MethodsT84 cells served as a colon model, while Caco-2 and 2D-organoids derived from human duodenum biopsies were used as small intestinal models. Epithelial monolayers grown on filter supports were challenged with EGCG and a combination of the two main IBD cytokines, tumor necrosis factor α (TNFα) and interferon γ (IFNγ). Barrier properties were monitored by measuring transepithelial resistance (TER), macromolecule permeability, apoptosis, and tight junction protein expression and localization.ResultsEGCG protected against barrier defects induced by TNFα and IFNγ. The cytokines decreased TER (T84: 11% ± 1% of initial value; Caco-2: 65% ± 2% of initial value; 2D-organoids: 57 ± 8 Ω*cm2 versus control 239 ± 29 Ω*cm2) which was prevented by 200 µM EGCG (T84: 89% ± 5%; Caco-2: 89% ± 3%; 2D-organoids: 343 ± 24 Ω*cm2; in all three models p < 0.001). In parallel, EGCG attenuated the cytokine-induced increase in macromolecular permeability by reducing apoptosis, as shown by reduced caspase-3 cleavage by >50% compared to cytokine-stimulated controls in all three models (p < 0.001). Furthermore, alterations in tight junction protein expression and localization contributed to barrier protection. In the small intestinal models, 200 µM EGCG stabilized barrier function, as demonstrated by an increase in TER (Caco-2: 105% ± 3% versus control 90% ± 3%; 2D-organoids: 182% ± 12% versus control 105% ± 2%, in both models p < 0.001), upregulation of claudin-4 (Caco-2: 140% ± 15%, p < 0.05; 2D-organoids: 115% ± 5%, p < 0.01) and reduced expression of claudin-2 (Caco-2: 75% ± 10%, p < 0.5; 2D-organoids: 66% ± 6%, p < 0.01) and claudin-7 (Caco-2: 64% ± 7%, p < 0.001; 2D-organoids: 65% ± 9%, p < 0.01). In the colon model, EGCG prevented the delocalization of claudin-1 and -5 that was induced by TNFα and IFNγ.ConclusionThe green tea component EGCG stabilizes the intestinal barrier and protects against barrier dysfunction induced by pro-inflammatory cytokines. These findings highlight the potential of EGCG as a supportive treatment strategy for IBD.